Effect of Metal Artifacts on Detection of Vertical Root Fractures Using Two Cone Beam Computed Tomography Systems - Safi, Yaser; Aghdasi, Mohammad Mehdi; Ezoddini-Ardakani, Fatemeh; Beiraghi, Samira; Vasegh, Zahra (Iranian Endodontic Journal, 2015)
Introduction: Vertical root fracture (VRF) is common in endodontically treated teeth. Conventional and digital radiographies have limitations for detection of VRFs. Cone-beam computed tomography (CBCT) offers greater detection accuracy of VRFs in comparison with conventional radiography. This study compared the effects of metal artifacts on detection of VRFs by using two CBCT systems. Methods and Materials: Eighty extracted premolars were selected and sectioned at the level of the cemento-enamel junction (CEJ). After preparation, root canals were filled with gutta-percha. Subsequently, two thirds of the root fillings were removed for post space preparation and a custom-made post was cemented into each canal. The teeth were randomly divided into two groups (n=40). In the test group, root fracture was created with Instron universal testing machine. The control teeth remained intact. CBCT scans of all teeth were obtained with either New Tom VGI or Soredex Scanora 3D. Three observers analyzed the images for detection of VRF. The sensitivity, specificity, positive predictive value (PPV) and negative predictive value (NPV) for VRF detection and percentage of probable cases were calculated for each imaging system and compared using non-parametric tests considering the non-normal distribution of data. The inter-observer reproducibility was calculated using the weighted kappa coefficient. Results: There were no statistically significant differences in sensitivity, specificity, PPV and NPV between the two CBCT systems. Conclusion: The effect of metal artifacts on VRF detection was not significantly different between the two CBCT systems. Keywords: Cast Post; CBCT; Cone-Beam Computed Tomography; Vertical Root Fracture